Influences of Friction stir tool parameters for joining two similar AZ61A alloy plates. (2022) - Haribalaji, V.; Boopathi, Sampath; Mohammed Asif, M.; Jeyakumar, M.; Subbiah, Ram; Anton Savio Lewise, K.
Abstract: The welding of magnesium alloy plates is highly important to utilize lightweight applications such as aircraft, automotive, and space sectors. In this research, Friction stir welding (FSW) of two similar AZ61A Magnesium alloy plates has been performed to obtain the maximum micro-hardness and tensile strength. The tool parameters such as tool revolving speed, Tool traveling speed, tool force, tool pin, and shoulder diameters have been modified during the welding experiments. The percentage of contributions and significant various tool parameters on micro-hardness and tensile strength have been analysed using Taguchi's technique. The tool pin diameter and tool revolving speed are highly contributed factors to enhance the micro-hardness and tensile strength than tool revolving speed and shoulder diameter. The predicted best tool parameters values have been evaluated by confirmation experiments.